Zebrafish Models of Cardiac Disease: From Fortuitous Mutants to Precision Medicine. Issue 12 (10th June 2022) - González-Rosa, Juan Manuel
Abstract : Heart disease is the leading cause of death worldwide. Despite decades of research, most heart pathologies have limited treatments, and often the only curative approach is heart transplantation. Thus, there is an urgent need to develop new therapeutic approaches for treating cardiac diseases. Animal models that reproduce the human pathophysiology are essential to uncovering the biology of diseases and discovering therapies. Traditionally, mammals have been used as models of cardiac disease, but the cost of generating and maintaining new models is exorbitant, and the studies have very low throughput. In the last decade, the zebrafish has emerged as a tractable model for cardiac diseases, owing to several characteristics that made this animal popular among developmental biologists. Zebrafish fertilization and development are external; embryos can be obtained in high numbers, are cheap and easy to maintain, and can be manipulated to create new genetic models. Moreover, zebrafish exhibit an exceptional ability to regenerate their heart after injury. This review summarizes 25 years of research using the zebrafish to study the heart, from the classical forward screenings to the contemporary methods to model mutations found in patients with cardiac disease. We discuss the advantages and limitations of this model organism and introduce the experimental approaches exploited in zebrafish, including forward and reverse genetics and chemical screenings. Last, we review the models used to induce cardiac injury and essential ideas derived from studying natural regeneration. Studies using zebrafish have the potential to accelerate the discovery of new strategies to treat cardiac diseases.